FAO fisheries report N.565 (FAO, 1997)
This document is the final of the seventh session of the Committee for the Development and Management of Fisheries in the Southwest Indian Oceanof the IOFC, which was held in Mahé ( Seychelles), from 29 September to 2 October 1997. Major topics were major developments since the sixth session; trends and issues in fisheries in the region; future cooperation in fisheries development and management in the region, implementation of the Code of Conduct for Responsible Fisheries; evaluation of the structure and functions for strenge of the Committee; and review of options for the future of the Committee. The summary of the main recommendations and dicisions is shown in Appendix E